IMPLEMENTASI PROGRAM ONE MAN ONE RESEARCH SEBAGAI STRATEGI PENINGKATAN MOTIVASI BELAJAR SISWA DI SMA NEGERI BALI MANDARA - Rita Tresnayani, Ni Nyoman; Suastika, I Nengah; Utami, Anak Agung Istri Dewi Adhi (Program Studi PPKn Universitas Pendidikan Ganesha, 2026)
Low student learning motivation, particularly in scientific research activities, remains a significant challenge in secondary education. This condition highlights the need for school programs that actively engage students and foster a strong academic research culture. This study aims to examine the philosophical and sociological foundations of the One Man One Research program, describe its implementation in improving students’ learning motivation, and analyze the supporting and inhibiting factors in its implementation at SMA Negeri Bali Mandara. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data analysis was conducted using an interactive analysis model consisting of data collection, data reduction, documentation, and conclusion drawing. The findings indicate that the One Man One Research program has been implemented systematically and sustainably as a flagship school program. The program contributes positively to enhancing students’ learning motivation by promoting active involvement in research activities, strengthening academic responsibility, and developing students’ independence and self-confidence. Supporting factors include strong school commitment, the role of research supervisors, and adequate facilities, while inhibiting factors involve students limited initial understanding of scientific research, tendencies to procrastinate, and psychological challenges related to the boarding school environment. Therefore, the One Man One Research program plays a significant role in improving students’ learning motivation at SMA Negeri Bali Mandara.